OCCURRENCE AND SEASONAL DYNAMICS OF CESTODE OF GENUS COTUGNIA DIAMARE, 1893 FROM GALLUS DOMESTICUS (International Journal of Food and Nutritional Sciences, 2022)
This investigation deals with the occurrence and seasonal dynamics of cestode parasite, Cotugnia, Diamare 1893 from the intestine of Gallus domesticus, at different collection sites of Umarkhed and allied area (M.S.) India during June 2021 to May 2022. The high incidence of infection of Cotugnia was recorded in summer season (72.5%) followed by winter season (45.00%) whereas infection was low in monsoon season (30.00%) respectively.